2013
DOI: 10.2139/ssrn.2269075
|View full text |Cite
|
Sign up to set email alerts
|

Equity Extraction and Mortgage Default

Abstract: Using a property-level data set of houses in Los Angeles County, I estimate that 30% of the recent surge in mortgage defaults is attributable to early home-buyers who would not have defaulted had they not borrowed against the rising value of their homes during the boom. I develop and estimate a structural model capable of explaining the patterns of both equity extraction and default observed among this group of homeowners. In the model, most of these defaults are attributable to the high loan-to-value ratios g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Using this information, I show that the three‐year foreclosure rate associated with equity extractions secured against MPDU properties increases by roughly 1.5 to 2 percentage points relative to equity extractions secured against non‐MPDU properties following the expiration of the price control. This result is consistent with previous findings regarding the increased risks associated with debt‐financed home equity extraction and suggests that borrowers are unlikely to be reinvesting all of the proceeds into more‐liquid assets, as their risk of foreclosure would presumably remain unchanged if that were the case (Mian and Sufi (), Bhutta and Keys (), Laufer ()).…”
supporting
confidence: 91%
“…Using this information, I show that the three‐year foreclosure rate associated with equity extractions secured against MPDU properties increases by roughly 1.5 to 2 percentage points relative to equity extractions secured against non‐MPDU properties following the expiration of the price control. This result is consistent with previous findings regarding the increased risks associated with debt‐financed home equity extraction and suggests that borrowers are unlikely to be reinvesting all of the proceeds into more‐liquid assets, as their risk of foreclosure would presumably remain unchanged if that were the case (Mian and Sufi (), Bhutta and Keys (), Laufer ()).…”
supporting
confidence: 91%
“…Laufer () also includes a default penalty to match data on default rates among underwater borrowers, which in his model takes the form of a higher rent‐price ratio for defaulters relative to nondefaulters. However, he estimates an extremely large default penalty that corresponds to 29% of permanent income.…”
mentioning
confidence: 99%
“…Mian and Sufi (2011) found that about 40 percent of new mortgage defaults during the housing crisis were driven by active home equity extraction. Using a sample of homeowners from California, Laufer (2011) notes that even after a precipitous decline in house prices during the bust, a vast majority of homeowners who defaulted would still have had positive equity had they not engaged in aggressive home equity extraction during the boom.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the paper exploits the policy discontinuity around the Texas border to identify the causal effect of home equity extraction on mortgage default 1 Regulations to limit initial mortgage debt used to purchase a home have long existed in countries such as Austria, Poland, China, and Hong Kong. 2 Laufer (2011) used a property level dataset from California and simulated the impact of Texas' home equity withdrawal restrictions on default rates, but did not directly estimate the impact of Texas' restrictions.…”
Section: Introductionmentioning
confidence: 99%